2016
DOI: 10.1038/srep25405
|View full text |Cite
|
Sign up to set email alerts
|

Highly Visible Light Responsive, Narrow Band gap TiO2 Nanoparticles Modified by Elemental Red Phosphorus for Photocatalysis and Photoelectrochemical Applications

Abstract: This paper reports that the introduction of elemental red phosphorus (RP) into TiO 2 can shift the light absorption ability from the UV to the visible region, and confirmed that the optimal RP loading and milling time can effectively improve the visible light driven-photocatalytic activity of TiO 2 . The resulting RP-TiO 2 nanohybrids were characterized systematically by a range of techniques and the photocatalytic ability of the RP-TiO 2 photocatalysts was assessed further by the photodegradation of a model R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(111 citation statements)
references
References 28 publications
(52 reference statements)
8
102
1
Order By: Relevance
“…In recent years, elemental semiconductor photocatalysts, such as sulfur and red phosphorus (RPh), have been explored as highly visible light active photocatalysts because of their suitable band gap that can cover the maximum part of the solar spectrum 28 29 30 31 32 33 . Among them, RPh has attracted considerable attention because of its earth abundance, low cost, good stability, and suitable band position, and thus it can make an efficient heterojunction with other materials, such as nickel(II) hydroxide, carbon-based composite, yttrium(III) phosphate microspheres, etc., and enhance the life time of the charge carriers 29 34 35 .…”
mentioning
confidence: 99%
“…In recent years, elemental semiconductor photocatalysts, such as sulfur and red phosphorus (RPh), have been explored as highly visible light active photocatalysts because of their suitable band gap that can cover the maximum part of the solar spectrum 28 29 30 31 32 33 . Among them, RPh has attracted considerable attention because of its earth abundance, low cost, good stability, and suitable band position, and thus it can make an efficient heterojunction with other materials, such as nickel(II) hydroxide, carbon-based composite, yttrium(III) phosphate microspheres, etc., and enhance the life time of the charge carriers 29 34 35 .…”
mentioning
confidence: 99%
“…37 Figure 11 shows the Nyquist plots of dummy cells with different work electrodes measured at 0 V bias in dark. The inset in Figure 11 presents the equivalent circuit by ZView 2 software fitting, and the electron dynamic parameters calculated from the fitted spectra are listed in Table I.…”
Section: Raman Spectra-as Shown Inmentioning
confidence: 99%
“…The of peaks broaden with increasing wt% of AgNPs which may be due to the increasing the size of synthesized nanoparticles. Reports reveal on broadening of peaks and red-shift of surface Plasmon spectra of AgNPs lead to the increasing size of AgNPs [53,54]. Ahmad et al [53] observed a red shift during the synthesis of gold nanoparticles for size dependant catalytic activity.…”
Section: Spectroscopic Investigationmentioning
confidence: 99%